Kualitas Produk dan Persepsi Harga terhadap Keputusan Pembelian - Bagus Imansyah; Hery Pudjoprastyono (IPM2KPE, 2023)
The purpose of this study was to analyze the influence of product quality and price perceptions on smartphone purchasing decisions (a case study of East Java